A Two-Sided Interval Iterative Method for the Finite Dimensional Nonlinear Systems (Journal of Computational Mathematics, 2021)
For the nonlinear system $$x=g(x)+h(x)+c, x\in R^n,$$ where $g$ and $h$ are isotone and antitone mappings respectively, a two-sided interval iterative method is presented, the initial condition of the two-sided iterative method is relaxed, and the convergence of the two methods are proved.